Advanced take-off and flight control algorithms for fixed wing unmanned aerial vehicles - De Hart, Ruan Dirk (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.